Fermentation of white and brown rice water increases plant nutrients and beneficial microbes - Nabayi, Abba; Boon, Christopher Sung Teh; Kee, Ali Zuan Tan; Ngai, Paing Tan (Universiti Putra Malaysia, 2022)
The wastewater after washing rice grains is known as washed rice water (WRW). WRW is often recommended for reuse as plant fertilizer, but little is known about the difference in the nutrient and microbial contents of WRW between white and brown rice. The study aims to answer this question and determine how much the nutrient contents in the WRW would change with fermentation and how fermentation would affect the phosphorus (P)- and potassium (K)-solubilization bacteria in the WRW. Medium-grained rice was washed at a volumetric rice-to-water ratio of 1:3 for 90 seconds at 0.357 × g. WRW was then fermented for 0 (fresh), 3, 6, and 9 days. The rice grains and WRW were analyzed for pH, electrical conductivity (EC), carbon (C), nitrogen (N), sulfur (S), ammonium (NH4+), nitrate (NO3-), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), copper (Cu), zinc (Zn), and boron (B), as well as for total microbial population and P- and K-solubilizing bacteria. Brown rice grains had 26 to 324% higher P, K, Mg, and Zn than white rice. Nutrient contents in the WRW increased with increasing fermentation, except for C, which decreased with fermentation. At 9 days of fermentation, P, Ca, Mg, Cu, and B in the white rice water increased by 4 to 207%, which were also higher than in the brown rice water. The microbial population increased with fermentation for 3 days, then decreased after that, following the same C trend in the WRW from both rice types. P-and K-solubilization by bacteria in the WRW from both rice types increased with fermentation. The P solubilization was 25% higher in brown rice water, while the K solubilization was 67% higher in white rice water. Fermented rice water from white and brown rice was revealed to potentially improve plant growth and increase overall soil health due to their plant nutrient and microbial contents.